More on Min-Max Allocation - Porteus, Evan L.; Yormark, Jonathan S. (Management Science, 1972)
In a preceding paper Jacobsen [Jacobsen, S. 1971. On marginal allocation in single constraint min-max problems. Management Sci. (July).] shows that marginal allocation solves a class of discrete, single constraint, min-max allocation problems. A dual approach, to this problem is presented, based on a generalization of Jacobsen's P condition, which should prove more efficient when many marginal improvement iterations would be required. A variant of sequential search by bisection is applied, possibly augmented by an accelerated marginal allocation scheme, in which finite convergence to an optimum solution is guaranteed.